2022
DOI: 10.3389/fpos.2022.977764
|View full text |Cite|
|
Sign up to set email alerts
|

Labor market situation of refugees in Europe: The role of individual and contextual factors

Abstract: The paper sheds light on the patterns of labor market integration of refugees in Western countries, who arrived primarily during the 2015–2016 mass refugee migration. Its major focus lies on the role of individual and contextual factors responsible for refugees' success in the labor market. At the host country level, the extent of permeability along the ethnic lines and the welcome of reception—both on the part of the majority population and the part of the established minorities—constitute further essential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 158 publications
(237 reference statements)
4
22
0
Order By: Relevance
“…Focusing on two of the three overarching clusters of explanatory characteristics (Huddleston et al, 2013), we showed which policy and individual characteristics explain these changes, partly through (re)gaining resources (Hobfoll, 2001). All in all, our findings indicate policy matters (see also: Kosyakova and Kogan, 2022). We find that a longer stay in reception centers reduces the chance of being employed (see also: de Vroome and van Tubergen, 2010;Bakker et al, 2014;Hainmueller et al, 2016;Hvidtfeldt et al, 2018;Kosyakova and Brenzel, 2020).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Focusing on two of the three overarching clusters of explanatory characteristics (Huddleston et al, 2013), we showed which policy and individual characteristics explain these changes, partly through (re)gaining resources (Hobfoll, 2001). All in all, our findings indicate policy matters (see also: Kosyakova and Kogan, 2022). We find that a longer stay in reception centers reduces the chance of being employed (see also: de Vroome and van Tubergen, 2010;Bakker et al, 2014;Hainmueller et al, 2016;Hvidtfeldt et al, 2018;Kosyakova and Brenzel, 2020).…”
Section: Discussionsupporting
confidence: 54%
“…Yet, unlike other migrants, refugees, and especially those who have recently arrived, are highly subject to such policies in most European countries. Such settlement policy characteristics could hamper or promote refugees' resource gathering and consequently their labor market participation (Kogan, 2007;Kanas and Steinmetz, 2021;Kosyakova and Kogan, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, e.g., migrants being mainly employed in low-skilled jobs (Arici et al 2019 ; Kosyakova and Kogan 2022 ), receiving lower payment (Kosyakova and Kogan 2022 ; Moyce and Schenker 2018 ), facing greater risk of health hazards at work (Malhotra et al 2013 ; Moyce and Schenker 2018 ; Yanar et al 2018 ) and being more likely to suffer from exploitation and abuse (Moyce and Schenker 2018 ). Migrants from low- and middle-income countries (Hargreaves et al 2019 ) as well as women (Kosyakova and Kogan 2022 ; Moyce and Schenker 2018 ; Rubiales-Gutiérrez et al 2010 ) are particularly affected. These adverse working conditions might impact mental health (Hargreaves et al 2019 ; Malhotra et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These adverse working conditions might impact mental health (Hargreaves et al 2019 ; Malhotra et al 2013 ). In addition, migrants and especially refugees (due to the flight experience itself (Heeren et al 2014 ; Kosyakova and Kogan 2022 ) and a subsequent asylum process in the host country that may be experienced as traumatic (Laban et al 2004 )) are generally considered particularly vulnerable in terms of their mental health. In various studies, migrants reported higher prevalence rates of post-traumatic stress disorder (PTSD) (Close et al 2016 ) and lower general and mental health (Arici et al 2019 ) compared to natives.…”
Section: Introductionmentioning
confidence: 99%